The contextual interview: a cross-cutting patient-interviewing approach for social context - Amber Cahill; Matthew Martin; Bridget Beachy; David Bauman; Jordan Howard-Young (Medical Education Online)
Patient interviewing pedagogy in medical education has not evolved to comprehensively capture the biopsychosocial model of healthcare delivery. While gathering a patient’s social history targets important aspects of social context it does not adequately capture and account for the real-time reassessment required to understand evolving factors that influence exposure to drivers of health inequities, social determinants of health, and access to supports that promote health. The authors offer a patient interviewing approach called the Contextual Interview (CI) that specifically targets dynamic and ever-changing social context information. To substantiate the use of the CI in medical education, the authors conducted a qualitative review of the Accreditation Council for Graduate Medical Education Milestones for primary care specialties (Family Medicine, Internal Medicine, and Pediatrics). Milestones were coded to the extent to which they reflected the learner’s need to acknowledge, assess, synthesize and/or apply patient contextual data in real-time patient encounters. Approximately 1 in 5 milestones met the context-related and patient-facing criteria. This milestone review further highlights the need for more intentional training in eliciting meaningful social context data during patient interviewing. The CI as a cross-cutting, practical, time-conscious, and semi-structured patient interviewing approach that deliberately elicits information to improve the clinician’s sense and understanding of a patient’s social context. The authors reviewed future directions in researching adapted versions of the CI for undergraduate and graduate medical education.